Implementation of IFRS 13 fair value measurement : issues and challenges faced by the Islamic financial institutions in Malaysia - Nathasa Mazna Ramli,; Abdul Rahim Abdul Rahman,; Ainulashikin Marzuki,; Marziana Madah Marzuki,; Wan Amalina Wan Abdullah@Wan Muda, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Fair value (FV) is claimed to be superior to other forms of measurement mainly because the former is easily understood by investors and stakeholders. However, the challenges faced in deploying International Financial Reporting Standards (IFRS) 13 FV Measurement could result in inconsistent application and unexpected costs related to the requirements of the standard. As such, this study explored the issues and challenges of implementing IFRS 13 FV Measurement faced by financial instruments, particularly within the context of Islamic Financial Institutions (IFIs). Upon adopting the qualitative approach, in-depth interview sessions were held with several academicians, accountants, auditors, and professional body representatives. The study outcomes revealed that issues in implementation of FV measurement were related to the relevance of measurement and hierarchy of level of FV measurement. Notably, issues pertaining to FV measurement were highlighted from the Shariah perspective. Valuable insights on the issues revolving around IFRS 13 implementation, particularly on financial instruments in Malaysia, are presented in this study.